Question from Yahoo Answer!


Number 1)

\sqrt{b+3} + \sqrt{b} = 3

(b+3) + b + 2\sqrt{(b+3)b} = 9

2b+3+2\sqrt{(b+3)b}=9

2\sqrt{(b+3)b}=6-2b

\sqrt{(b+3)b}=3-b

(b+3)b=9+{b^2}-6b

{b^2}+3b=9+{b^2}-6b

9b = 9

b = 1

number 2)
\sqrt{4x-3}=2+\sqrt{2x-5}

\sqrt{4x-3}-\sqrt{2x-5}=2

(4x-3)+(2x-5)-2\sqrt{(4x-3)(2x-5)}=4

6x-8-4=2\sqrt{(4x-3)(2x-5)}

6x - 12 = 2\sqrt{(4x - 3)(2x - 5)}

3x - 6 = \sqrt{8{x^2}-26x+15}

9{x^2} - 36x + 36 = 8{x^2} - 26x + 15

{x^2} - 10x + 21 = 0

(x - 7)(x - 3) = 0

x = 3 or x = 7

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s